2008
DOI: 10.3892/mmr_00000010
|View full text |Cite
|
Sign up to set email alerts
|

The allelic distribution of a single nucleotide polymorphism in the PDCD5 gene locus of Japanese non-small cell lung cancer patients

Abstract: Abstract. It has been reported that the rs1862214 single nucleotide polymorphism (SNP) in the programmed cell death 5 gene (PDCD5) is associated with smoking-related lung cancer risk and prognosis in a European population with a history of smoking. The aim of this study was to investigate the status and impact of SNPs in the PDCD5 locus of a Japanese population. We developed an assay based on realtime PCR with melting curve analysis for determining the rs1862214 SNP, and examined this SNP in 165 lung cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…An analogous study found similar results for this SNP and its influence on susceptibility to chronic myeloid leukemia (14). Despite these findings, a correlation between this particular SNP and lung cancer susceptibility was not seen in a Japanese population (15).…”
Section: Introductionsupporting
confidence: 54%
“…An analogous study found similar results for this SNP and its influence on susceptibility to chronic myeloid leukemia (14). Despite these findings, a correlation between this particular SNP and lung cancer susceptibility was not seen in a Japanese population (15).…”
Section: Introductionsupporting
confidence: 54%
“…In a previous study, we also did not find effect on Aβ species and tau/p-tau [9] . These markers, however, may provide novel insight into AD pathology and its progression [16] , [18] , [26] . The biomarkers reflecting specific AD pathology in CSF (Aβ and tau/p-tau) change over the disease course in a pattern that does not reflect neurodegeneration in a simple way making them less suitable for longitudinal markers of disease progression [27] , [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of these two pathways caused drug induced apoptosis, hence the high presence of f-circRNAs in leukemic cells will have a negative effect on treatment response. This could be an indicator of possible treatment failure for leukemic patients (Nanba and Toyooka, 2008).…”
Section: Several Reported Circrnas Contribute To Treatment Resistance Via Pi3k/akt Pathwaymentioning
confidence: 99%